DEVELOPMENT OF FORCE ANALOGY METHOD FOR ACTIVE VIBRATION CONTROL OF FRAMES - SHEIKHZADEH YAZD, IRAJ TOLOUE (2018)
Maintaining the man made structures is one of the main concerns of engineers all over the world. Although many methods and ways are introduced during the past years, but most of them are expensive and black boxes. In this study, an attempt has been made to control the frame displacement subjected to earthquake ground motion. Some facts such as limitation of control systems in dissipating energy, unknown power of earthquakes, and structural aging, lead to nonlinear analysis and damaged members.